Integration of ocean color data, thermal sensor data and environmental parameters for assessment of productivity of the coastal water. - Khaing, Myint Myint
Oceans occupy almost 70 percent of the Earth's surface, which play an important role in the climate conditions of the adjacent land regions. In the ocean, the physical, chemical and biological processes are linked in an intimate manner. Oceanic features such as chlorophyll concentration, current boundaries, sea surface temperature, ocean fronts and eddies, suspended particulate matter and dissolved organic matter influence the ocean environment in a complex manner. Satellites are used as an important tool for better understanding of the marine processes, ecology and the coastal environment. In the present study the in situ data collected off Goa, west coast of India, the World Ocean Atlas data and the satellite data have been taken for analysis. The main data base consists of phytoplankton, Nitrate, Phosphate, Silicate, Temperature, Oxygen and pH which collected by the month of November, 1999. The surface and bottom data have been averaged to represent the mean concentration of the mixed layer depth of the region. Appropriate weightage have been assigned to the chemical, biological and physical parameters to find out the productive regions. The in-situ data and the World Ocean Atlas data have been integrated and analyzed to produce the final Productivity Map off Goa, west coast of India. The NOAA-AVHRR data of the month of April 2003 has been used for retrieval of sea surface temperature. The phytoplankton concentration map of same day from IRS-P4 (OCM) data has also been used for analysis. The OCM data and AVHRR data have been analyzed for identification of Productive Zones of the coastal regions which will be a helpful methodology for Potential Fishing Zone (PFZ) prediction.
Keywords: Environmental parameters; IRS-P4 (OCM).; NOAA-AVHRR.; PFZ